The Implementation of Zoning System Policy on The Admission Process of New Student in Public Junior High School - Ariswati, Yuvita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Government policy on the implementation of zoning has been described based on circular letter number 01 of 2019 and number 420/2973/SJ on the acceptance of new learners addressed to the governor and regent or mayor throughout Indonesia to establish zoning in the implementation of PPDB. The purpose of this research is to: 1) to know the implementation of the zoning system policy on the admission of new learners (PPDB) level of public junior high school 10 Jember 2019/2020 school year. 2) To know the opinions of the community (parents) on the implementation of the zoning system policy on the acceptance of new learners (PPDB) level of junior high school in public junior high school 10 Jember school year 2019/2020. The research methods in this study use a type of qualitative descriptive research with normative and empirical approaches. The data collection techniques used are library studies and field studies with observations, interviews, and documentation. The analysis of data in this study uses inductive qualitative data analysis, data or information that has been selected collected and then grouped according to the details of each issue. The results showed that: 1) the implementation of the zoning system policy on the admission process of new students (PPDB) at SMPN 10 Jember school year 2019/2020 has been running according to technical instructions issued by the education office of Jember district. 2) The admissions process of new students (PPDB) consists of achievement track (5%), parent or guardian's duty transfer path (5%), zoning line (90%). 3) Students who enter using the zoning path do not use the value as a reference receipt. 4) Public opinion reveals the expectation of continuing the zoning system's policy with some evaluation that builds a better.